DyeVert Contrast Reduction System Use in Patients Undergoing Coronary and/or Peripheral Angiography: A Systematic Literature Review and Meta-Analysis - Tarantini, Giuseppe; Prasad, Anand; Rathore, Sudhir; Bansal, Shweta; Gottfried, Regine; Rosenkranz, Alexander R.; Briguori, Carlo; Yaghoubi, Mohsen; Mashayekhi, Atefeh; Javanbakht, Mehdi; Moloney, Eoin (Frontiers in Medicine, 2022)
Background: Contrast-associated acute kidney injury (CA-AKI) is an important adverse effect associated with injecting iodinated intra-arterial contrast media (CM) during coronary angiography. The DyeVertTM Contrast Reduction System is a medical device intended to reduce the intra-arterial CM volume (CMV) administered. The aim of this study was to assess DyeVert System clinical effectiveness and safety by implementing a systematic review and meta-analysis of existing evidence. Methods: Systematic electronic literature searches were conducted in MEDLINE, Embase, the Cochrane Database of Systematic Reviews, ClinicalTrials.gov, and the International Clinical Trials Registry Platform database. Relevant data were extracted from included studies and meta-analyses were performed to synthesize evidence across studies. Results: The review included 17 eligible studies involving 1,731 DyeVert System cases and 1,387 control cases (without the use of DyeVert). Meta-analyses demonstrated use of the DyeVert System reduced CMV delivered to the patient by 39.27% (95% CI, 36.10%-42.48%, P<0.001), reduced CMV/baseline renal function ratios (Hedges’s g, -0.56; 95% CI, -0.70 to -0.42, P<0.001) and percentage of cases exceeding the maximum CMV threshold (risk difference -0.31, 95% CI, -0.48 to -0.13, P<0.001) while maintaining adequate image quality in 98% of cases. DyeVert System cases demonstrated lower CA-AKI incidence versus controls (absolute risk reduction 5.00% (95% CI, 0.40%-9.80%; P=0.03), relative risk 0.60 (95% CI, 0.40-0.90; P= 0.01) with a pooled estimate of the number needed to treat with the DyeVert System to avoid 1 CA-AKI event of 20. Conclusions: DyeVert System use significantly reduces CMV delivered to the patient, CMV/baseline renal function ratios, and CA-AKI incidence while maintaining image quality. Accordingly, the device may serve as an adjunctive, procedure-based strategy to prevent CA-AKI. Future multi-center studies are needed to further assess effects of minimizing CMV on endpoints such as CA-AKI prevention, incidence of adverse cardiac and renal events, and health care costs.